Constructs of "Development" among CDC faculty and in students student research studies - Cagasan, Editha G.; Palis, Ricamela; Rodrigo, Frederick F.; Monthivuth, Ker; Reyes, Laureano U.; Ocampo, Lalaine B.; Bugas, Marie; Lumanta, Melinda F. (2008)
The plurality of realities influencing the constructs of development among development communicators prompted the conduct of this research project. Content analysis, meta-research, and discourse analysis were used to answer the question: What are the constructs of development that have emerged among the students and faculty of the College of Development Communication (CDC) from 1972 to 2004? Ninety-nine graduate and 93 undergraduate research manuscripts and the transcripts of the focus group discussion (FGD) participated in by selected CDC faculty were analyzed.

Three major themes of development emerged from the FGD transcripts and research manuscripts, namely: Theme 1 - as improvement; Theme 2 - as a goal; and Theme 3 - as a process. Parallel constructs of development among the faculty, graduate and undergraduate students were revealed by the research studies and the FGD. THEME 1 was most dominant during the "department years," although this is still popular at present. Theme 2 become popular during the "institute years," but it acquired a spectrum of meanings through time. Although it was still anchored on the economic dimension, humanistic and holistic views begs to co-exist with the economic roots of development. Theme 3 started to gain grounds during the "department years," but it gained wider acceptance during the "college years."

The emerging constructs of development were reflected in the accommodation of subjects, issues, and concerns other than agriculture and agricultural productivity, such as health, education, religion, environment and others. All these ushered in changes in research methods and focus. These provide evidence that there had been attempts to bring in the multiplicity of new constructs of development in the study and practice of development communication.
Keywords: Communication; Communications research